2018
DOI: 10.1371/journal.pone.0197678
|View full text |Cite
|
Sign up to set email alerts
|

Deviance sensitivity in the auditory cortex of freely moving rats

Abstract: Deviance sensitivity is the specific response to a surprising stimulus, one that violates expectations set by the past stimulation stream. In audition, deviance sensitivity is often conflated with stimulus-specific adaptation (SSA), the decrease in responses to a common stimulus that only partially generalizes to other, rare stimuli. SSA is usually measured using oddball sequences, where a common (standard) tone and a rare (deviant) tone are randomly intermixed. However, the larger responses to a tone when dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 45 publications
(107 reference statements)
2
37
1
Order By: Relevance
“…While organisms must be able to undergo SSA, they must also be able to quickly detect changes that differ from what has recently been experienced (or what can thereby be predicted), as it may signal salient information. This ability of neurons and neural systems to detect abrupt, unexpected variation from the constant, expected sensory milieu (or a set of presented stimuli) is known as deviance detection (DD) and typically involves an increase in firing responses (Malmierca et al, 2009;Antunes et al, 2010;Hamm and Yuste, 2016;Musall et al, 2017;Parras et al, 2017;Polterovich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While organisms must be able to undergo SSA, they must also be able to quickly detect changes that differ from what has recently been experienced (or what can thereby be predicted), as it may signal salient information. This ability of neurons and neural systems to detect abrupt, unexpected variation from the constant, expected sensory milieu (or a set of presented stimuli) is known as deviance detection (DD) and typically involves an increase in firing responses (Malmierca et al, 2009;Antunes et al, 2010;Hamm and Yuste, 2016;Musall et al, 2017;Parras et al, 2017;Polterovich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in anesthetized rats showed enhanced EP response to deviant tones across different sleep states (including REM and non-REM sleep) in the auditory cortex [31]. Other studies reported sensitivity of EPs to deviant tones in primary auditory cortex [32]. However, the role of subcortical structures in SG has not yet been elucidated.…”
Section: Auditory Filtering Capacities Of Mgbmentioning
confidence: 93%
“…3 showing that, without any parameter tuning, the NMC model replicates rather successfully diverse aspects of SSA. Specifically, that the response of the neurons is significantly higher to the deviant than to the standard tone 1,[3][4][5]13,14,29,31,35 , that this difference depends on the probability of the deviant 1,14,35 , and that the response to the deviant is larger than the response to the same tone when it is presented among many tones with denselypacked frequencies -the 'diverse narrow' paradigm 4,13,14 . Furthermore, in some cases, the response for a rarely presented tone ('deviant alone' or 'rare') were smaller than the responses to the same tone presented as a deviant accompanied by a standard tone 4,13,14 .…”
Section: Figure 2 Stimulus-specific Adaptation Emerges In the Modelementioning
confidence: 99%
“…We attempted to replicate as closely as possible the in vivo experimental protocols used to explore SSA in rodent auditory cortex 4,5,13,14,29,35,67 . To achieve this, two tones f1 = 6,666 Hz and f2 = 9,600 Hz were selected as the base frequencies for our simulations; these frequencies are separated by 0.52 octaves around the center frequency of the simulated cortical circuit (8,000 Hz); see Fig.…”
Section: Ssa Protocolsmentioning
confidence: 99%
See 1 more Smart Citation